Small non coding RNAs in adipocyte biology and obesity - Amri, Ez-Zoubir; Scheideler, Marcel (Molecular and cellular endocrinology, 2017)
Obesity has reached epidemic proportions world-wide and constitutes a substantial risk factor for hypertension, type 2 diabetes, cardiovascular diseases and certain cancers. So far, regulation of energy intake by dietary and pharmacological treatments has met limited success. The main interest of current research is focused on understanding the role of different pathways involved in adipose tissue function and modulation of its mass. Whole-genome sequencing studies revealed that the majority of the human genome is transcribed, with thousands of non-protein-coding RNAs (ncRNA), which comprise small and long ncRNAs. ncRNAs regulate gene expression at the transcriptional and post-transcriptional level. Numerous studies described the involvement of ncRNAs in the pathogenesis of many diseases including obesity and associated metabolic disorders. ncRNAs represent potential diagnostic biomarkers and promising therapeutic targets. In this review, we focused on small ncRNAs involved in the formation and function of adipocytes and obesity.